Development of adaptive seed-separation trier for small-seeded crops - Aliiev, Elchyn; Алієв, Ельчин Бахтияр огли; Lupko, Kristina; Лупко, Кристина Олегівна; Kobets, Oleksandr; Кобець, Олександр Миколайович (Transilvania University Press, 2023)
The STAR-CCM+ software package was used to create a model of the process of separating seed material from small-seeded crops on a cylindrical cellular trier. By taking into account the physic-mechanical properties of mustard seeds and the given initial and boundary conditions of the trier, a visualization of the separation process was obtained, which depended on several factors, including the number of seeds and impurities in the seed mixture, the rotation frequency of the trier cylinder, and the diameter of the trier cylinder. The numerical simulation of the process at a variable rotation frequency resulted in obtaining a relationship between the number of seeds and impurities, the relative content of impurity elements in the seed mixture in the tray, and the conditional performance of the separator, depending on the duration of cylinder rotation counterclockwise and clockwise. Based on the obtained dependencies of the numerical modeling and the results of the improvement of the TracTrac software package, a laboratory sample of an adaptive cylindrical cell trier was developed. This trier allows real-time, based on the received video image, to determine the trajectory of the seed flight and to control the position of the tray and the rotation frequency of the cylinder using Arduino UNO. За допомогою програмного комплексу STAR-CCM+ створено модель процесу сепарації посівного матеріалу дрібнонасіннєвих культур на циліндричному комірковому трієрі. Враховуючи фізико-механічні властивості зерен гірчиці та задані початкові та граничні умови трієру, було отримано візуалізацію процесу сепарації, яка залежала від кількох факторів, у тому числі кількості зерен та домішок у насіннєвій суміші, частота обертання трієрного циліндра та діаметр трієрного циліндра. У результаті чисельного моделювання процесу при змінній частоті обертання отримано залежність між кількістю насіння і домішок, відносним вмістом домішкових елементів у насіннєвій суміші в лотку та умовною продуктивністю сепаратора залежно від тривалості обертання циліндра проти і за годинниковою стрілкою. На основі отриманих залежностей чисельного моделювання та результатів удосконалення програмного комплексу TracTrac розроблено лабораторний зразок адаптивного циліндричного коміркового трієра. Цей трієр дозволяє в режимі реального часу на основі отриманого відеозображення визначати траєкторію польоту насіння та контролювати положення лотка та частоту обертання циліндра за допомогою Arduino UNO.
Розробка адаптивного трієра для сепарації насіння для дрібнонасіннєвих культур
Keywords: separation; сепарація; seed; насіння; length; довжина; trier; трієр; modeling; моделювання; parameters; параметри; adaptive; адаптивний